(untitled) (Research, Society and Development, 2022)
Systemic arterial hypertension is a multifactorial clinical condition characterized by high blood pressure levels. This project refers to a bibliographic review of the Brazilian scientific literature on the benefits of physical exercise for hypertensive elderly people. This subject has been highlighted in the health sector, since the incidence of elderly people affected by hypertension has been increasing. To carry out this work, scientific articles were used with topics related to hypertension in the elderly correlated with the benevolent effects of physical exercises on the specificity of this group. For the treatment of pathology, there are two ways, depending on the patient’s degree and age, namely: pharmacological treatment and non-pharmacological treatment, which can be carried out by physical exercises, to which the studies in this work are attributed. The objective was to understand the various benefits of physical exercise for the elderly who have hypertension. According to bibliographic studies, it is possible to show that Physical Education can promote health improvement in the quality of life, among other benefits, which include the control and treatment of systemic arterial hypertension. For theoretical basis, scientific articles were used with content on quality of life, health correlated to Physical Education, physical activities, hypertension and the elderly. Finally, the research found that physical exercise, when applied effectively, provides the elderly with a highly positive treatment against increased blood pressure, in addition to offering them a better quality of life.